2014
DOI: 10.1182/blood-2013-10-533398
|View full text |Cite
|
Sign up to set email alerts
|

CD16xCD33 bispecific killer cell engager (BiKE) activates NK cells against primary MDS and MDSC CD33+ targets

Abstract: Key Points NK cells and their expression of FcRγIII (CD16) are decreased in MDS and inversely correlate with a substantial increase in MDSCs. CD16xCD33 BiKE potently activates blood and marrow MDS-NK cells at all diseases stages to lyse CD33+ MDS and CD33+ MDSC targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
169
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(171 citation statements)
references
References 53 publications
1
169
0
1
Order By: Relevance
“…Several previous studies in MDS found deficient NK cell responses against various autologous or allogeneic tumor targets. 11,12,19,20 The present study suggests that NK cell defects can, in the majority of cases, be attributed to inefficient or defective NK cell differentiation, leading either to a predominantly immature NK cell compartment or to an overall lack of NK cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies in MDS found deficient NK cell responses against various autologous or allogeneic tumor targets. 11,12,19,20 The present study suggests that NK cell defects can, in the majority of cases, be attributed to inefficient or defective NK cell differentiation, leading either to a predominantly immature NK cell compartment or to an overall lack of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in line with those of a recent study that found strongly reduced NK cell frequencies in a high-risk (presumably pretreated) cohort of MDS patients undergoing hematopoietic stem cell transplantation from unrelated donors. 20 Since NK cells are an important component of immunological tumor surveillance, it is tempting to speculate that a lack of NK cells in MDS patients increases the risk of leukemic progression to acute myeloid leukemia. In this regard, NK cells were previously implicated in relapse control following allogeneic hematopoietic stem cell transplantation for myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…In leukemia, miR-29b has been shown to alter the capacities of NK cells, which disrupts the innate immune response and allows LSCs to escape surveillance [28]. Correspondingly, reduced NK function is seen in MDS patients as the disease progresses [29], and synthetic reactivation of NK cell activity has been explored as a potentially therapeutic treatment [30]. With respect to signaling, cytokine stimulation and differentiation of NK cell populations has been shown to enhance NK cell response and functionality [31].…”
Section: Fig 1 a Immune Cells Act As Homeostatic Plasticizers Of Thementioning
confidence: 99%
“…изучали NK-клетки и МС при МДС. Выяснилось, что содержание NK-клеток и экспрессия CD16 на их поверхности снижаются при МДС и одновременно повышается число MC по сравнению со здоровыми донорами [79]. X. Chen и соавт.…”
Section: Hla-drunclassified